Student’s Perception on the Use of Fun Vocabulary Multimedia in Enhancing Vocabulary Mastery for Elementary Level - Eka Surya Fitriani; Virdyra Tasril; Ade Rizka (International Journal of English and Applied Linguistics (IJEAL), 2023)
The developments of multimedia language learning after Covid Pandemic. With the rise of the Internet and new technology, given students' perception about the use of Fun Vocabulary, their experience in the sector is critical for the successful development of academic programs, since the end user's perception toward the application of information technology is one of the most effective aspects. Hence this study was conducted in purpose to evaluate the students’ perception on the usage of multimedia Fun Vocabulary for grade IV elementary students as the implementation of Computer Assisted Language Learning (CALL). Twenty students filled the questionnaire survey after they experienced learning within the multimedia in case to assess the performance and qualities of a designed multimedia Fun Vocabulary. This study applied quantitative research to measure the users’ evaluation on platform usage through questionnaire which was as the instrument of collecting data. The result found that the students’ agreement showed positive perceptions prevailed over their disagreement or neutral responses in the questionnaire. Fun Vocabulary multimedia was designed and provided a variety of exercises and materials with interesting visual content which can enhance the understanding of vocabulary in English for elementary school level. It was very helpful for their motivation and interest to keep learning English via the platform and practice through its exercises. On the other side, the findings also indicated that the limitation of multimedia that cannot reach the next grade. On the other hand, other findings showed that the materials were very limited and could not reach more list of vocabulary provided in this multimedia. Otherwise, Fun Vocabulary multimedia simply can be used to learn English for students basically and can be useful for teacher as blended learning at class.